Performance of spray deposited Gd-doped barium cerate thin films for proton conducting SOFCs. Issue 4 (May 2015) - Dubal, S.U.; Bhosale, C.H.; Jadhav, L.D.
Abstract: Doped barium cerate is a promising solid electrolyte for intermediate temperature fuel cells as a protonic conductor. In the present paper, the nanocrystalline Gd-doped barium cerate (BaCe0.7 Gd0.1 Y0.2 O2.9 ) thin films have been successfully deposited on alumina substrate by spray pyrolysis technique. The films deposited from 0.1 M concentration and annealed at five different temperatures were characterized with different physio-chemical techniques. The BCGY is crystallized in orthorhombic perovskite structure with slight shift to the lower 2 θ value compared with barium cerate (BC) and yttrium doped barium cerate (BCY). The grain growth and hence densification is also investigated by using SEM and AFM. The grain growth is almost complete at 1000 °C and the surface of the film appears to be smooth with typical roughness of 152 nm. Raman spectrum of BCGY film shows intense band at 463.8 cm −1 compared to pure BC and BCY indicating the presence of more oxygen vacancies due to Gd doping. The proton conductivity of BCGY thin film in moist atmosphere is 1×10 −3  Scm −1 .